PENGARUH TERAPI RELAKSASI OTOT PROGRESIF TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI - Diah Khoirunisah; Destiawan Eko; Rina Puspitasari (Nusantara Hasana Berdikari, 2022)
Hypertension is a disease that affects many people around the world. According to the World Health Organization (WHO), about 40% of the adult population over the age of 25 years has been diagnosed with hypertension. Meanwhile, Indonesia has 55.2% of hypertension sufferers in the 55-64 year age range. The objective of this research is review the effect of progressive muscle relaxation therapy on reducing blood pressure in hypertensive patients. Literature Review researchers used databases such as Google Scholar, PubMed, Research Gate, and Elsevier. Thirty related journals were found and included in six journals. Based on a literature review of six inclusion articles that the authors reviewed, the results showed that there was an effect between progressive muscle relaxation therapy on reducing blood pressure by taking actions for 5-10 minutes and performed 3 times a day. The use of progressive muscle relaxation therapy can be used as an alternative/non-pharmacological intervention and can be implemented in patients with hypertension as an effort to lower blood pressure and provide a relaxing effect on the body.